The Implications of Endocrinology in Orthodontics - Literature Review - Kamal Adeel Tahir; Mahmood Hafiz Taha; Fida Mubassar (Balkan Stomatological Society, 2020)
Endocrinopathies have a variety of orofacial presentations which span from dental malocclusion to facial disfigurement. These characteristics depend on the nature and severity of the condition. An orthodontist should understand the body's physiological processes to be able to timely determine the optimum intervention and plan treatment stages accordingly in compromised individuals. Communication between the two specialties should be well coordinated and should help facilitate quality health care to the patient. This review was aimed to impart the basic knowledge and the pivotal guidelines for orthodontic management in these conditions. Systemic conditions require multidisciplinary management and the dental team should aim to provide quality oral health care to enhance the overall quality of life and the orthodontist plays a vital role in helping patients achieve physical and psychological health.